Hypothesis: Long non-coding RNA is a potential target of mycotoxins - You, Li; Wang, Xu; Wu, Wenda; Jaćević, Vesna; Nepovimova, Eugenie; Wu, Qinghua; Kuca, Kamil (Food and chemical toxicology, 2021)
The molecular target of mycotoxins is not fully understood. Extensive data derived from cell and animal experimental studies demonstrate that long non-coding RNAs (lncRNAs) play crucial roles in mycotoxin-induced toxicities. Mycotoxins stimulate the upregulation/downregulation of lncRNA expression, which further promote apoptosis, is related to the mTOR/FoxO signaling pathway, and contributes to tumor cell growth, death, and liver and chondrocyte damage. Moreover, lncRNA can establish interactions with NF-κB and cause immune evasion. These preliminary data suggest that lncRNAs are involved in potential upstream regulatory events and further regulate downstream apoptosis, oxidative stress, and anti-apoptotic events that affect cell death and survival. Therefore, we hypothesize that lncRNAs are potential targets of mycotoxins. Investigation of the expression of the potential target lncRNAs by mycotoxin-mediated stimulation, and exploration of the upstream and downstream relationship between lncRNA and the key proteins involved in mycotoxin toxicity, should be performed. This Hypothesis provides clues for further understanding of the molecular mechanisms of mycotoxins.
Keywords: oxidační stres; autofagie; Mycotoxins; Oxidative stress; Cell Line, Tumor; Toxicity mechanism; RNA dlouhá nekódující; RNA, Long Noncoding; Long non-coding RNA; Target; Animals; Autophagy; lidé; únik nádoru z imunitní kontroly; Humans; zvířata; apoptóza; nádorové buněčné linie; Oxidative Stress; Apoptosis; Tumor Escape; mykotoxiny